Zastosowanie rachunku kosztów cyklu życia w ocenie efektywności inwestycji polegających na budowie kogeneracyjnych źródeł energii - Wierzbiński, Marcin (The Application of Life Cycle Costing to Evaluating the Effectiveness of Investments in Co-Generation Power Plants, 2005)
In the article the author shows how way life cycle costing can be used to evaluate the effectiveness of investments in co-generation power plants. Firstly, there are presented the main characteristics of life cycle costing and the method of evaluating the effectiveness of investments called adjusted present value (APV). Then the author tries to apply these two instruments to evaluate the effectiveness of hypothetical investment in co-generation power plant.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Finanse Bankowość Rachunkowość (2); 2005; nr 1059, s. 297-312